Factors associated with sexually transmitted infections in sugarcane cutters: subsidies to caring for* - Juliana Pontes Soares; Sheila Araújo Teles; Karlla Antonieta Amorim Caetano; Thaynara Ferreira Amorim; Maria Eliane Moreira Freire; Jordana de Almeida Nogueira; Brunna Rodrigues de Oliveira; Oriana Deyze Correia Paiva Leadebal; Patricia da Silva Araújo; Ana Cristina de Oliveira e Silva (Universidade de São Paulo, 2020)
Objective: to estimate the prevalence of Sexually Transmitted Infections (STIs) and associated factors in sugarcane cutters. Method: a cross-sectional, analytical study with 937 sugarcane cutters from Paraíba and Goiás, states of Brazil, respectively. An outcome variable was the positive results in some rapid tests for HIV, syphilis, hepatitis B and C. Bivariate and multiple analyses were performed to identify the association between these infections and sociodemographic and behavioral variables. Results: all participants were male, most were young adults and had low schooling. Prevalence of STI was estimated at 4.1% (95% CI: 3.0-5.5). According to multiple regression analysis, the variables age over 40 years (OR 5.0; CI 95%: 1.8-14), alcohol consumption (OR 3.9; CI 95%: 1.3-11.9), and illicit drugs (OR 2.9; CI 95%: 1.3-6.3) were factors associated with the STIs investigated. On the other hand, having some religion (OR 0.4; CI 95%: 0.2-0.8), and work in the Midwest Region (OR 0.4; CI 95%: 0.2-0.9) were factors negatively associated with these infections. Conclusion: presence of risk behaviors for STI among sugarcane cutters. Screening for these infections in groups of rural workers is essential for early diagnosis and breaking the chain of transmission.